The Use of Modeling for Characterization of Membranes - Nidal Hilal (Membrane Characterization, 2017)
The typical characteristics of membranes can be estimated directly from experimental data. To successfully characterize membranes using such techniques a representative model of the membrane process must be used that is simple enough for solution yet detailed enough to capture the key characteristics required. Two cases have been considered where the membrane process has been characterized. The first case is for large pore membranes where slurry filtration or gel layers form on the membrane surface, which is quite typical for microfiltration and ultrafiltration processes. A simple model was described that considers the membrane resistance and the specific cake resistance. The experimental data required are outlined and worked examples are provided that show how to manipulate the data to capture the membrane characteristics. More intensive models that describe the complex microhydrodynamics and interfacial events occurring at the surface and within the small pore membranes are also described. These models are shown to be far more complex and the solution methodologies are not trivial. However, these methods are capable of providing characterization of the pore radius and electrical properties of the membrane at almost atomic scale dimensions. For the case of pore size characterization a simple analytical equation is available and a worked example is provided along with a narrative on best practice. The characterization of electrical properties is far more complicated and involves the solution of nonlinear differential equations. A solution methodology has been explained and tips on best practices have been provided. Overall, membrane characterization using models and experimental data has been demonstrated and can be used for the evaluation of novel membranes or as a guide for the scientist or engineer in the design, scale-up, and optimization of new membrane processes.